Application of a glycaemic control optimization programme in patients with stress hyperglycaemia. Issue 5 (28th October 2014) - Shi, Zeya; Tang, Siyuan; Chen, Yuxiang; Lee, Diana T‐F; Chair, Sek Y; Jiang, Bo; Zhu, Xu; Pan, Xiaoji; Yang, Jinxu; Qin, Yuelan
ABSTRACT: Background: Stress‐induced hyperglycaemia (SHG) can be observed in as high as 75% of critically ill patients, which can induce severe complications or adverse events. However, conventional intensive insulin therapy (CIIT) tends to induce hypoglycaemia and glucose variability. Aims: This study investigated the clinical effects of a blood glycaemic control optimization programme (BGCOP) in patients with stress hyperglycaemia post hepatobiliary or pancreatic surgery. Design: This study is a randomized, controlled, prospective clinical observation. Methods: Eighty‐six patients with postoperative SHG were randomly divided into a control and experimental groups. Participants in the control group underwent CIIT, while participants in the experimental group underwent blood glycaemic control optimization programme (BGCOP). A range of 7·8–10·0 mmol/L was designated as the target range for effective control of blood sugar. The validity index, adverse events and complications were compared between two groups. Results: Compared to participants treated with CIIT, participants treated with BGCOP reached the target range of blood sugar levels more quickly ( p = 0·000). The high glycaemic index ( p = 0·000), incidence of hypoglycaemia ( p = 0·011), and other adverse events as well as the incidence of abdominal infection ( p = 0·026), incision infection ( p = 0·044), and lung infection ( p = 0·047) were significantly lower in participants who underwent the BGCOP than in patients treated with CIIT. Conclusion: BGCOP can more effectively control blood sugar levels compared with CIIT in patients with SHG after hepatobiliary or pancreatic surgery. Relevance to clinical practice: This study provides a direction for blood glycaemic control in patients with stress hyperglycaemia post hepatobiliary or pancreatic surgery.